PROFESSIONALISM OF THE TEACHING STAFF AS THE SYNONYMOUS OF QUALITY OF EDUCATIONAL SERVICES - D.Kuatova,; A.Zhakupova,; Zh. Malgaraeva, (Academic Journal of Physical and Chemical Sciences, 2019)
This article sets out the criteria of professionalism of the teaching staff are outlined for use by state authorities, university management and consumers of educational services; measures are proposed to improve the professionalism of the teaching staff and thereby improve the quality of higher education. Purpose – identification of professionalism criteria of the teaching staff of a higher school and development of improvement ways. Methodology – methodological basis for the study are research works of home and foreign experts in the field of professional competence of university teachers, regulations and guidance documents governing the activities of a higher school in the Republic, results of student surveys. Originality/value – results of the study can be used by the teaching staff and the management of universities to develop measures aimed at improving the quality of teaching in higher educational institutions.